The influence of the friendship factor on social media on the intention to continue social shopping and social media participation: A study on generation Z - Wahyudi, Divaldi Altira; Daryanti, Sri (Interaction, Community Engagement, and Social Environment, 2025)
Background: Humans continue to revolutionize how they search for and process information in line with technological advancements, social changes, and evolving needs. However, amidst the openness of information, the friendship factor is often overlooked due to broad access to various sources without considering their credibility. This study aims to understand how the friendship factor, particularly informational social influence, interpersonal trust, and perceptions of a friend's knowledge, influences consumer behavior in the context of social shopping and social media participation. It also examines the role of confirmation and perceived usefulness in shaping consumer satisfaction and their impact on the intention to continue social shopping and social media participation, using an Expected Confirmation Model (ECM) adapted to consumer behavior. Method: This study employs a quantitative design with a single cross-sectional method and purposive sampling. Data were collected through a structured online questionnaire, yielding 274 respondents. The data were then analyzed using the Partial Least Square Structural Equation Model (PLS-SEM) technique. Findings: The findings reveal that informational influence, interpersonal trust, and perceived friend knowledge significantly affect confirmation (0.145–0.337), which in turn influences perceived usefulness (0.523–0.598), user satisfaction (0.347–0.473), and continuance intention of social shopping (0.204–0.513) and social media participation (0.113–0.532). The results of the study indicate that all hypotheses were accepted. Friendship factors, particularly interpersonal trust, play a crucial role in shaping perceived usefulness and experience confirmation, which in turn influence satisfaction and the intention to continue social shopping and social media participation. Conclusion: This study highlights the importance of providing positive experiences (positive confirmation) to encourage sustainable intentions in the context of social shopping and social media participation. Novelty/Originality of this article: The study introduces an adapted Expected Confirmation Model (ECM) to examine how friendship factors influence consumer satisfaction and continued intention in social shopping and social media participation.